(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to examine the effect of profitability, liquidity, firm size, and asset structure on firm value. Profitability is measured by price book value, liquidity is measured by current assets, company size is measured by natural logarithms, and asset structure is measured by fixed asset ratio. This research is a quantitative study. The sample of this research was obtained by purposive sampling technique, namely selecting the sample with predetermined criteria. Based on the purposive sampling method with predetermined criteria, 115 samples were obtained from 23 manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period. The method in this study was multiple regression analysis technique which was processed using the SPSS version 25 program. The results showed that profitability and firm size had a positive and significant effect on firm value in consumer goods companies. Meanwhile, liquidity and asset structure have no significant effect on firm value in consumer goods companies.